Парадигми процесного підходу в менеджменті: сутність та протиріччя - Рижакова, Г. М. (Ways to Improve Construction Efficiency, 2012)
Singled out two paradigms process approach to management. Considered basic traditional paradigm and defined its contradictions. Characteristic of modern management concept, which actually make up a new paradigm of process approach. Summarizes their differences and shortcomings.